The Effectiveness of Inklewriter Website to Increase the Recount Text Writing Skill of The Tenth Graders of SMKN 1 Mojosongo - Dewangga, Defian (Universitas Kristen Cipta Wacana, 2025)
Writing is one of the productive skills of English language learning that requires the ability to develop and organize ideas in a logical sequence. However, many students still have problems with writing a recount text. Their writing is often incoherent and not in a logical sequence of events. This problem highlights the need for new learning media that can assist students' writing processes. This study examined the effectiveness of the Inklewriter website in increasing students' recount text writing skill. The Inklewriter website is an interactive digital media platform applied throughout the entire writing process. The Inklewriter website is used for planning ideas, structuring text, and editing. This study employed a quasi-experimental non-equivalent control group design with purposive sampling. According to the data analysis, the Independent Sample T-test yielded a significance value <0.001, indicating a significant difference between the experimental and control groups. In addition, the increase in the experimental group's writing skill after using the Inklewriter Website was also determined to be significant, based on the effect size with a value of 1.519. The study demonstrates that utilizing the Inklewriter Website is effective in increasing students' recount text writing skills. This study shows that the Inklewriter Website, as a learning media, effectively increases students' recount text writing skill. The researcher also suggests that teachers and further study should examine the application of the Inklewriter Website to teach writing skill using other texts or in more specific contexts.